2022
DOI: 10.3390/cells11162617
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Strain Probiotic Formulation Improves Intestinal Barrier Function by the Modulation of Tight and Adherent Junction Proteins

Abstract: In healthy individuals, tight junction proteins (TJPs) maintain the integrity of the intestinal barrier. Dysbiosis and increased intestinal permeability are observed in several diseases, such as inflammatory bowel disease. Many studies highlight the role of probiotics in preventing intestinal barrier dysfunction. The present study aims to investigate the effects of a commercially available probiotic formulation of L. rhamnosus LR 32, B. lactis BL 04, and B. longum BB 536 (Serobioma, Bromatech s.r.l., Milan, It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…The LPS induced the expected TEER reduction only in the absence of HMC-1.2 ( Figure 1 and Figure 2 ), indeed, it has been reported to impair tight junction strength [ 28 , 29 , 30 , 31 ] via TLR4-dependent activation of the membrane-associated adaptor protein focal adhesion kinase in Caco-2 monolayers [ 32 ]. Interestingly, we showed that both the exposure to the probiotic formulation for 24 h, and the presence of HMC-1.2, concurred to preserve the integrity of the epithelial layer, as demonstrated by the TEER values in the Caco-2/HT-29 co-cultures.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The LPS induced the expected TEER reduction only in the absence of HMC-1.2 ( Figure 1 and Figure 2 ), indeed, it has been reported to impair tight junction strength [ 28 , 29 , 30 , 31 ] via TLR4-dependent activation of the membrane-associated adaptor protein focal adhesion kinase in Caco-2 monolayers [ 32 ]. Interestingly, we showed that both the exposure to the probiotic formulation for 24 h, and the presence of HMC-1.2, concurred to preserve the integrity of the epithelial layer, as demonstrated by the TEER values in the Caco-2/HT-29 co-cultures.…”
Section: Discussionmentioning
confidence: 79%
“…In particular, it modulates luminal metabolism, stabilizing the intestinal microbiota [ 47 ], and it is able to modulate the immune response in elderly patients if administered prior to the influenza vaccine [ 48 ]. Furthermore, this strain can stabilize tight junction proteins through exopolysaccharide and the production of butyrate, as active metabolites [ 28 , 49 ]. The influence of probiotics toward MCs was also demonstrated for the B longum KACC 91563, that induces MCs’ apoptosis [ 50 ], and for the probiotic formulation VSL#3, capable of reducing MC degranulation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the gut microbiota communicates with the host through various biomolecules, pathways independent of the signalling of nutrients and epigenetic mechanisms, an alteration of these communication pathways related to age-related intestinal dysbiosis can heavily influence the health and life span of the host and trigger an innate immune response [ 45 ]. The circulation of bacterial compounds in the host is probably due to the breakdown of the intestinal epithelial barrier caused by the silent chronic inflammation state, and greater intestinal permeability has been suggested as a potential source of age-related inflammation [ 64 , 65 , 66 ].…”
Section: Intestinal Microbiota and Systemic Protectionmentioning
confidence: 99%